New buffer layer for high-temperature superconducting ceramics on sapphire: LaBa2Cu3Oy/Ag bilayers - Nakamura, O.; Chan, I.; Guimpel, J.; Schuller, I.; Guimpel, Julio (AIP Publishing, 1991)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of California; Estados Unidos